Pengaruh Media Terhadap Identitas Budaya Lokal Melayu Palembang - Reza Aprianti; M. Mifta Farid (President University, 2018)
Mass media has a function in human life that is as information channel, perform functions as educators, to provide entertainment and as a media persuasive. It is from this function that this study will raise the preparation of how the mass media influence on local cultural identity. Media Television is the object of research is local television in South Sumatra using quantitative research methodology. The theory that made in this research is adolescent with level of education sma. The results of this study can be influence although not very significant between the influence of media and adolescent understanding of local culture.